2013
DOI: 10.1310/tsr2003-226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horseback Riding Therapy on Quality of Life in Patients Post Stroke

Abstract: Supplementation of conventional physiotherapy with HBRT, applied in different contexts, may yield positive QOL outcomes for people with stroke. We recommend that further studies be carried out to clarify the benefits of HBRT applied singly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 21 publications
0
54
0
5
Order By: Relevance
“…H-RT involves rhythmic movement of the horse, which continually challenges the rider's posture and gives vestibular, proprioceptive, and visual input that may facilitate the observed improvements in gait and balance seen in the H-RT group. 11 On the contrary, R-MT involves repeated motor skill training, postural stability, and weight shifting, in combination with rhythmic, coordinated hand movements that tentatively facilitate the improvements in balance and grip strength seen in the R-MT group. The observed improvements in working memory in the R-MT group may reflect the cognitively challenging nature of R-MT.…”
Section: July 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…H-RT involves rhythmic movement of the horse, which continually challenges the rider's posture and gives vestibular, proprioceptive, and visual input that may facilitate the observed improvements in gait and balance seen in the H-RT group. 11 On the contrary, R-MT involves repeated motor skill training, postural stability, and weight shifting, in combination with rhythmic, coordinated hand movements that tentatively facilitate the improvements in balance and grip strength seen in the R-MT group. The observed improvements in working memory in the R-MT group may reflect the cognitively challenging nature of R-MT.…”
Section: July 2017mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] These interventions share important core components but differ from each other with respect to their combinations of Background and Purpose-Treatments that improve function in late phase after stroke are urgently needed. We assessed whether multimodal interventions based on rhythm-and-music therapy or horse-riding therapy could lead to increased perceived recovery and functional improvement in a mixed population of individuals in late phase after stroke.…”
mentioning
confidence: 99%
“…22,27,28 One study 41 did not have a confirmed PEdro score and it was calculated independently by two authors and disagreements were resolved by discussion. Eleven studies 23,24,26,[29][30][31]34,[42][43][44][45] did not perform an intention to treat analysis. More than 15% of loss to follow-up occurred in four studies.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…One study each reported that no adverse events 25 and no serious adverse events occurred. 37 Seventeen studies [22][23][24]26,27,[29][30][31][32][33][34][35][36]39,[43][44][45] , including ten with exercise components, did not state whether any adverse events occurred or not.…”
Section: Quality Of Evidencementioning
confidence: 99%
“…Houve uma ampliação no seu conceito, e se pode mensurar qualidade de vida por meio da avaliação da funcionalidade e dos estados físico, psicológico e social. (23) Podemos dizer que as mudanças físicas, psicológicas e sociais, provindas do processo de envelhecimento podem afetar na qualidade de vida do idoso, se o mesmo não tiver um suporte para enfrentar essas mudanças. Assim investigar a Qualidade de Vida em idosos é fundamental (24) Nessa revisão foi possível verificar que apesar de muitos artigos abordarem a qualidade de vida, em sua maioria tratavam de adultos, e apenas um estudo investigou sobre os efeitos da Equoterapia na Qualidade de Vida de indivíduos idosos.…”
Section: Equoterapia E Qualidade De Vidaunclassified